Palmitic acid induces intestinal lipid metabolism disorder, endoplasmic reticulum stress and inflammation by affecting phosphatidylethanolamine content in large yellow croaker Larimichthys crocea - Fang, Wei; Liu, Yongtao; Chen, Qiuchi; Xu, Dan; Liu, Qiangde; Cao, Xiufei; Hao, Tingting; Zhang, Lu; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2022)
In the 21st century, intestinal homeostatic imbalance has emerged as a growing health challenge worldwide. Accumulating evidence reveals that excessive intake of saturated fatty acid (SFA) induces intestinal homeostatic imbalance. However, the potential molecular mechanism is still unclear. In the present study, we found that palm oil or palmitic acid (PA) treatment disturbed lipid metabolism homeostasis and triggered endoplasmic reticulum (ER) stress and inflammation in the intestine or intestinal cells of large yellow croaker (Larimichthys crocea). Interestingly, PA treatment significantly decreased phosphatidylethanolamine (PE) content in the intestinal cells. PE supplementation decreased triglyceride content in the intestinal cells induced by PA treatment by inhibiting fatty acid uptake and lipogenesis. PE supplementation suppressed ER stress. Meanwhile, PE supplementation alleviated inflammatory response through p38 MAPK-p65 pathway, reducing the damage of intestinal cells caused by PA treatment to some extent. Our work revealed that intestinal homeostatic imbalance caused by PA treatment was partly due to the decrease of PE content. PE consumption might be a nutritional strategy to regulate intestinal homeostasis in fish and even human beings.